2019
DOI: 10.1371/journal.pone.0217640
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-based lung tumor culture on porous PLGA microparticle substrates

Abstract: Scaffold-based cancer cell culture techniques have been gaining prominence especially in the last two decades. These techniques can potentially overcome some of the limitations of current three-dimensional cell culture methods, such as uneven cell distribution, inadequate nutrient diffusion, and uncontrollable size of cell aggregates. Porous scaffolds can provide a convenient support for cell attachment, proliferation and migration, and also allows diffusion of oxygen, nutrients and waste. In this paper, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…High-magnification images revealed that the surfaces of the MPs were smooth and that 1-10 µm open pores resulting from rapid solvent extraction in the PLGA hardening process were distributed on the surfaces. The porous surface morphology corresponded to previous studies of PLGA microparticles fabricated using a W 1 /O/W 2 double emulsion solvent evaporation technique [20][21][22][23]. This porous surface morphology played an important role in the drug-release process.…”
Section: Morphologysupporting
confidence: 82%
“…High-magnification images revealed that the surfaces of the MPs were smooth and that 1-10 µm open pores resulting from rapid solvent extraction in the PLGA hardening process were distributed on the surfaces. The porous surface morphology corresponded to previous studies of PLGA microparticles fabricated using a W 1 /O/W 2 double emulsion solvent evaporation technique [20][21][22][23]. This porous surface morphology played an important role in the drug-release process.…”
Section: Morphologysupporting
confidence: 82%
“…Yip and Cho observed significant Dox resistance of HepG2 human hepatocellular liver carcinoma spheroids cultured in collagen gel (∼100% viability) compared to spheroids not cultured in collagen gel (∼20% viability) (Yip and Cho, 2013) while Liu M. et al (2018) observed that human ovarian cancer cell line OV-2008 became much more resistant to carboplatin, 5-fluorouracil and Ptx when cultured in a collagen matrix compared to cells cultured in the absence of collagen. Similarly, in our previous screening study using A549 cells cultured on fibronectin-coated porous PLGA microparticles, a two to fourfold higher drug resistance to Cis, Ptx, Dox, Gem, Cur, and 5-fluorouracil was observed when compared to 2D cultures (Kuriakose et al, 2019). This trend has been observed not just for lung cancer cultures but also for other cancer 3D models.…”
Section: Discussionsupporting
confidence: 69%
“…The eventual release of these highly concentrated degradation products upon complete polymer degradation will affect cell viability. On the other hand, the pores in PPMS provide channels for the catalytic degradation products to seep out thus resulting in comparatively intact morphology (Lu et al, 2000;Siepmann et al, 2005;Wu and Ding, 2005;Yang et al, 2008;Pan and Ding, 2012;Kuriakose et al, 2019). The greater decrease in weight of PPMS with time in Figure 4B could be explained by the removal of degradation byproducts during the washing step at each timepoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have employed the stromal component of the tissue's matrix to serve as the base platform. Various approaches taken to mimic several features of the TME in 3D models include the development of tumor spheroids [84], the design of scaffoldbased TME models [85], patient-derived xenograft systems where cells isolated from patients are incorporated into rodents for investigative purposes [86], organoids that can be self-organized into desirable tissue phenotypes and mimic the functionality of an organ while expressing one or more cell types [87], highly maneuverable microfluidic systems [88], and more recently 3D bio-printing platforms that can recreate the TME under highly controllable parameters yielding tailored 3D tissue architecture [89]. Although each 3D model has its pros and cons, studying disease pathology in glandular or stratified tissues has become extremely convenient using these systems [37].…”
Section: Mimicking Tme In Three-dimensionsmentioning
confidence: 99%